Effect of aerobic exercise and low-carbohydrate high-fat diet on glucose tolerance and android/gynoid fat in overweight/obese women: A randomized controlled trial - Valsdottir, Thorhildur Ditta; Øvrebø, Bente; Kornfeldt, Thea Martine; Litleskare, Sigbjørn; Johansen, Egil Ivar; Henriksen, Christine; Jensen, Jørgen (Frontiers in Physiology, 2023)
The study was designed to compare the effects of weight loss induced by a low-carbohydrate-high-fat diet or a normal diet, with and without exercise, on glucose tolerance, and android (A) and gynoid (G) fat distribution. The study was registered at clinicaltrials.gov; NCT04100356. In total, 57 women classified as overweight or obese (age 40 ± 3.5 years, body mass index 31.1 ± 2.6 kg/m2) were randomly assigned and completed a 10-week intervention using a low-carbohydrate high-fat diet or a normal diet, with or without aerobic interval exercise. An equal deficit of 700 kcal/day was prescribed, either restricting the diet only, or moderately restricting diet and including three 50-minute high-intensity bicycle sessions per week. There were thus four groups: normal diet (NORM); low-carbohydrate-high-fat diet (LCHF); normal diet with exercise (NORM-EX); and low-carbohydrate-high-fat diet with exercise (LCHF-EX). To assess differences between groups we used linear mixed models. With all groups pooled, the intervention resulted in a weight loss of 6.7 ± 2.5% (p < 0.001). Prior to the intervention a strong inverse correlation was observed between cardiorespiratory fitness and glucose tolerance. The intervention did not result in differences between groups in area under the curve in glucose, nor in fasting glucose, Homeostatic Model Assessment for Insulin Resistance or Matsuda Insulin Sensitivity Index. Post-intervention android fat was lower in LCHF than NORM (3223 ± 727 vs. 2533 ± 535 g, p=0.041). LCHF reached a lower A/G ratio than NORM (0.94 ± 0.12 vs. 1.04 ± 0.09, p=0.011) and LCHF-EX (0.94 ± 0.12 vs. 1.09 ± 0.09, p<0.001) after the intervention. An effect of diet was seen, in which LCHF resulted in lower android fat mass compared to NORM and the lowest A/G ratio compared to the other matched groups, but with no accompanying improvement in AUC glucose. In conclusion, although all groups achieved within-group improvements in response to the intervention, no superior effect on glucose tolerance was observed with the LCHF diet, with or without exercise.